2009
DOI: 10.1159/000219681
|View full text |Cite
|
Sign up to set email alerts
|

α-Crystallin Downregulates the Expression of TNF-α and iNOS by Activated Rat Retinal Microglia in vitro and in vivo

Abstract: Purpose: Inhibition of microglial activation has become an important strategy to attenuate neurotoxic damage to the central nervous system. We evaluated the effects of α-crystallin on the production of cytokines in lipopolysaccharides (LPS) and optic nerve injury-activated retinal microglia. Methods: Microglia were collected from retinas of newborn rats, cultured and treated with LPS in vitro. Microglia were also activated by an optic nerve crush in vivo. Pretreatments with and without α-crystallin were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…Previous studies showed an important role of iNOS and COX-2 in the pathogenesis of RGC loss after crush injury [15, 17, 19, 37]. NO produced by iNOS in activated inflammatory cells, microglia or injured neurons contributes to cytotoxicity resulting in neuron death and axonal damage [38, 39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed an important role of iNOS and COX-2 in the pathogenesis of RGC loss after crush injury [15, 17, 19, 37]. NO produced by iNOS in activated inflammatory cells, microglia or injured neurons contributes to cytotoxicity resulting in neuron death and axonal damage [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive Muller cell and astrocyte upregulating GFAP and become hypertrophic in response to injury [13, 14]. Activated glia has been showed to release multiple inflammatory mediators, such as TNF-α, IL-6, IL-1β, MCP-1, iNOS, and COX-2 [1519]. Nitric oxide synthase inhibitors and anti-inflammatory cytokines have been used to rescue RGC from apoptosis through inhibiting microglial activation after axon injury [2022].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, alpha-crystallin administration prior to, or at the time of the injury, prevented retinal ganglion cell axon degeneration and decreased microglial activation, as shown by prevention of the upregulation of TNF-alpha and iNOS production (Wu et al 2009; Ying et al 2008). Interestingly, another set of publications demonstrated that fragments of alpha- or beta-crystallin could regulate crystallin functions, including their chaperone function.…”
Section: Crystallins and Therapiesmentioning
confidence: 97%
“…In crystallin treated animals, RGC numbers in animals injured by optic nerve crush were significantly increased compared to that in saline-injected group: 124±26 cells/mm 2 , 128±31 cells/mm 2 , and 164±20 cells/mm 2 were survived in animals treated with 0.05 g/kg, 0.5 g/kg and 5 g/kg of alpha crystallin, respectively. The cell protective effect of alpha crystallin was aassociated with the inhibition of microglial activation and TNF-α/iNOS release (Wu et al, 2009; 2014). …”
Section: Crystallins Support Rgc Survival and Axon Regenerationmentioning
confidence: 99%